Curcumin Analogs, PGV-1 and CCA-1.1 Exhibit Anti-migratory Effects and Suppress MMP9 Expression on WiDr Cells - Febri Wulandari; Muthi' Ikawati; Mitsunori Kirihata; Jun-Ya Kato; Edy Meiyanto (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Colon cancer is still a crucial concern in the development of chemotherapeutic drugs due to the drug resistance phenomenon and various side effects to patients. One of the newest compound that show anticancer activities against several cancer cells, Chemoprevention Curcumin Analog 1 (CCA-1.1), has increasingly been explored to overcome the limitation of conventional drugs.METHODS: We evaluated the anti-migratory effect of CCA-1.1 and Pentagamavunone-1 (PGV-1) by using WiDr colon cancer cells. The expression profiles of Tumor Protein 53 (TP53) and Matrix Metalloproteinase-9 (MMP9) in colon cancer were obtained from the UALCAN database. Survival outcomes of TP53 and MMP9 in colon cancer patients were analyzed using the Kaplan-Meier method. We used 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT), scratch wound healing, and gelatin zymography assays to observe the cytotoxic effect, anti-migratory activity, and MMP9 expression, respectively, in CCA-1.1 or PGV-1-treated cells.RESULTS: Level of MMP9 was found significantly overexpressed in the primary tumor and metastasis nodal, while TP53 mutation sample types were observed and influenced the survival outcome in colon cancer patients. CCA-1.1 and PGV-1 exhibited strong cytotoxic activity after 24 and 48 h treatment against WiDr cells. The migration assay demonstrated that PGV-1 and CCA-1.1 at 1 mM inhibited cell migration up to 40% after 48 h in single and combination with doxorubicin. The MMP9 expression was significantly inhibited by 0.5 mM CCA-1.1.CONCLUSION: This study emphasizes that the anti-migratory effect of CCA-1.1 is better than PGV-1 via MMP9 suppression on WiDr. Thus, CCA-1.1 is prominent to be developed as an anti-metastatic agent.KEYWORDS: chemopreventive curcumin analog 1.1 (CCA-1.1), PGV-1, WiDr cells, anti-migration, MMP9